Anomalous non-equilibrium response in black phosphorus to sub-gap mid-infrared excitation - Montanaro, Angela; Giusti, Francesca; Zanfrognini, Matteo; Di Pietro, Paola; Glerean, Filippo; Jarc, Giacomo; Rigoni, Enrico Maria; Mathengattil, Shahla Y.; Varsano, Daniele; Rontani, Massimo; Perucchi, Andrea; Molinari, Elisa; et al. (Nature Communications, 2022)
The competition between the electron-hole Coulomb attraction and the 3D dielectric screening dictates the optical properties of layered semiconductors. In low-dimensional materials, the equilibrium dielectric environment can be significantly altered by the ultrafast excitation of photo-carriers, leading to renormalized band gap and exciton binding energies. Recently, black phosphorus emerged as a 2D material with strongly layer-dependent electronic properties. Here, we resolve the response of bulk black phosphorus to mid-infrared pulses tuned across the band gap. We find that, while above-gap excitation leads to a broadband light-induced transparency, sub-gap pulses drive an anomalous response, peaked at the single-layer exciton resonance. With the support of DFT calculations, we tentatively ascribe this experimental evidence to a non-adiabatic modification of the screening environment. Our work heralds the non-adiabatic optical manipulation of the electronic properties of 2D materials, which is of great relevance for the engineering of versatile van der Waals materials.
CRIS-Team Scopus Importer:2022-07-20